2019
DOI: 10.1177/0897190019853979
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Stewardship During Critical Illness: A Call to Action

Abstract: Intravenous fluids (IVFs) are the most common drugs administered in the intensive care unit. Despite the ubiquitous use, IVFs are not benign and carry significant risks associated with under- or overadministration. Hypovolemia is associated with decreased organ perfusion, ischemia, and multi-organ failure. Hypervolemia and volume overload are associated with organ dysfunction, delayed liberation from mechanical ventilation, and increased mortality. Despite appropriate provision of IVF, adverse drug effects suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 76 publications
1
56
0
1
Order By: Relevance
“…Managing volume status in patients with critical illness is a dynamic and delicate exercise that necessitates frequent monitoring and sound clinical judgment 21 .The "fluid balance method" is the approach most widely used for managing volume replacement by fluid infusion during intensive care or perioperatively. Perceived needs and losses are summarized continuously and volume is substituted with crystalloids and colloids in proportion to their respective plasma-volumeexpanding properties.…”
Section: Fluid Balancementioning
confidence: 99%
See 2 more Smart Citations
“…Managing volume status in patients with critical illness is a dynamic and delicate exercise that necessitates frequent monitoring and sound clinical judgment 21 .The "fluid balance method" is the approach most widely used for managing volume replacement by fluid infusion during intensive care or perioperatively. Perceived needs and losses are summarized continuously and volume is substituted with crystalloids and colloids in proportion to their respective plasma-volumeexpanding properties.…”
Section: Fluid Balancementioning
confidence: 99%
“…It is well known that fluid overload, positive fluid balance, morbidity and mortality are interrelated. Organ dysfunction, prolonged mechanical ventilation, and higher mortality may result from volume overload and hypervolemia 21,22 . When compared with zero fluid balance, positive fluid balance after cardiac surgery was associated with increased incidence of acute kidney injury (AKI) 30 , suggesting that fluid retention may be causally interrelated with AKI, contributing to renal retention and weight gain.…”
Section: Fluid Balancementioning
confidence: 99%
See 1 more Smart Citation
“…It is known that induced thoracic hypervolemia increases mechanical respiratory workload and airway pressure, even in normal individuals (25). It is also well known that hypervolemia and volume overload are associated with increased organ dysfunction in critically ill patients, increased weaning time and total time of weaning, as well as an increase in infectious complications and mortality (26). The effects of hypervolemia on the outcomes of critically ill patients have been investigated in medical patients, although there is a paucity of studies in this field.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of hypervolemia on the outcomes of critically ill patients have been investigated in medical patients, although there is a paucity of studies in this field. In a study involving 144 patients underwent emergency surgery, Barmparas et al (26) could find no effect of positive fluid balance on total mortality (11% negative fluid balance vs 15.5% positive fluid balance, p = 0.422), but when evaluated together with other accompanying factors, negative fluid balance was found to provide survival benefit by 70% in the first five days of surgery and negative fluid balance on the first day of surgery provided survival benefit, but also reduced infectious complications [95% confidence interval 0.63 (0.45, 0.88); p= 0.006 and 0.64 (0.46, 0.90); p=0.010 respectively) (26). In the same study, MV time and length of ICU stay were found to be longer in patients with a positive fluid balance and prolonged MV was found to be an independent risk factor for mortality in of surgical patients.…”
Section: Discussionmentioning
confidence: 99%